Pengaruh Lingkungan Kerja Fisik Dan Disiplin Kerja Terhadap Kinerja Pegawai Kecamatan Pasar Kemis Kabupaten Tangerang - Putri Amaliah Nurul Fathonah; Suwanto Suwanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study is to determine the effect of physical work environment and work discipline on the performance of employees at the Pasar Kemis District Office. This research uses a quantitative method. The sampling technique employed is saturated sampling with a total of 40 respondents. The data analysis used in this study is multiple linear regression analysis. The results of this study indicate that the physical work environment has a significant effect on employee performance. The regression equation is Y = 21.742 + 0.410X1, with a correlation value of 0.598, meaning that the two variables have a moderate relationship. The coefficient of determination is 0.357 or 35.7%, which means that the physical work environment contributes 35.7% to employee performance. The hypothesis test shows a t-value of 4.595 > t-table of 1.686. Thus, H0 is rejected and H1 is accepted. Work discipline also affects employee performance, with the regression equation Y = 19.961 + 0.465X2. The correlation coefficient is 0.683 or 68.3%, indicating the contribution of work discipline to employee performance. Based on the t-test results, the t-value is 5.766 > t-table 1.686 with a significance value of 0.000 < 0.05, so H0 is rejected and H2 is accepted. Simultaneously, the physical work environment and work discipline influence employee performance, with the regression equation Y = 4.789 + 0.421X1 + 0.474X2. The correlation coefficient is 0.918, indicating a very strong relationship. The coefficient of determination is 0.843 or 84.3%, while the remaining 15.7% is influenced by other variables. The F-test shows an F-value of 99.059 > F-table 3.259 with a significance level of 0.000 < 0.05. Thus, H0 is rejected and H3 is accepted, meaning that simultaneously there is a significant effect of the physical work environment and work discipline on employee performance at the Pasar Kemis District Office.